Influence of dietary 1αlpha-hydroxycholecalciferol, individually or in combination with microbial phytase in calcium and phosphorus deficient diets on growth performance and tibia parameter of Japanese quails (Coturnix japonica) - Farshd Kheiri; Mohammad Poshtvar; Sayed Mohammad Ali Jalali Haji Abadi; Nasir Landy (Acta Scientiarum. Animal Sciences, 2018)
The effect of 1α-OH-D3 in calcium-phosphorus (Ca-P) deficient diets on Japanese quail growth performance and tibia parameters was investigated. Eight-day-old (n = 160) newly hatched quails were weighed and randomly allocated to 20 groups, each with 4 replicate pens of 8 birds. Treatments were as follows: T1, Ca-P-adequate; T2,Ca-P-deficient; T3, Ca-P-deficient + 500 FTU kg-1 of phytase (Ph); T4, Ca-P-deficient diet + 5 µg kg-1 of 1α-OH-D3; T5,Ca-P-deficient + Ph + 5 µg kg-1 of 1α-OH-D3. Results showed that quails fed Ca-P-adequate had significantly higher body weight compared with quails fed Ca-P-deficient, Ca-P deficient supplemented with 1α-OH-D3 and Ca-P-deficient supplemented with 1α-OH-D3 and phytase, but did not differ from Ca-P-deficient diet supplemented with phytase. Quails fed Ca-P deficient were unable to achieve FCR comparable to quails fed Ca-P-adequate (p < 0.05). The percentage of bone ash data indicated that quails fed Ca-P-adequate had higher tibia ash compared with other groups except for quails fed Ca-P deficient diet supplemented with combination of 1α-OH-D3 and phytase. Quails fed Ca-P-adequate had higher tibia P compared with quails fed Ca-P-deficient. In conclusion, these results indicated that quails fed Ca-P-deficient supplemented with 5 µg kg-1 of 1α-OH-D3 in combination of 500 FTU kg-1 of phytase were able to achieve the same tibia ash and Ca compared with quails fed Ca-P-adequate.